Endoparasitic Mites (Rhinonyssidae) on Urban Pigeons and Doves: Updating Morphological and Epidemiological Information - Jesús Veiga; Ivan Dimov; Manuel de Rojas (Diversity, 2020)
Rhynonyssidae is a family of endoparasitic hematophagous mites, which are still largely unknown even though they could act as vector or reservoir of different pathogens like dermanyssids. Sampling requirements have prevented deeper analysis. Rhinonyssids have been explored in a few host specimens per species, leading to undetailed morphological descriptions and inaccurate epidemiology. We explore the relationships established between these parasites in two Columbiformes urban birds (domestic pigeon (Columba livia domestica) and Eurasian collared dove (Streptopelia decaocto)), assesing 250 individuals of each type in Seville (Spain). As expected, Mesonyssus melloi (Castro, 1948) and Mesonyssus columbae (Crossley, 1950) were found in domestic pigeons, and Mesonyssus streptopeliae (Fain, 1962) in Eurasian collared doves. However, M. columbae was found for the first time in Eurasian collared doves. This relationship could be common in nature, but sampling methodology or host switching could also account for this result. An additional unknown specimen was found in a Eurasian collared dove, which could be a new species or an aberrant individual. We also provide an epidemiological survey of the three mite species, with M. melloi being the most common one followed by M. streptopeliae and M. columbae. High variation between previous epidemiological measurements and ours highlights the importance of developing deeper studies to uncover the factors regulating mite prevalence and intensities of infection.